PEMBERDAYAAN NELAYAN MELALUI PENGOLAHAN IKAN PASCA PRODUKSI - Pratomo, Heru (INOTEKS: Jurnal Inovasi Ilmu Pengetahuan,Teknologi, dan Seni, 2003)
The activities of this technology application purpos~ : (1) gives skills in fish processing to the wife of fisherman in Trisik Beach.Desa  Banaran, Kecamatan Galur, Kabupaten Kulon Progo, especially to make bandengfish  presto,  fish meatballs, fish noodles, fish shredded, and fish ketchup; (2) increase the fisherman income by means of fish processing.These activities are followed by 14 women, and carried out in three days in Trisik. The methods of this activity are talkactive and practice in fish processing.  The topics of the talk~cti~e are:   (1) The contents of nutrient in fish, (2) Fish processing technology,  (3) The health technology in food processing, (4) The sanitation of area manufacture, (5) Analysis in exertion fish processing, and (6) The methods of packing production  and getting sertificate from Health Department. The topics in practice of fish processing  are  making  bandeng fish  presto,  fish meatballs,  fish  noodles,  fish shredded, and fish ketchup. ,The 'results 6f'these  activities  indicate that the participants  are very interest. The  participants   are  interesting   in  the  processing  of  bandeng fish  presto,   fish meatballs, and fish noodles.  The conclucions of these activities are: (I)  the activities have succeeded agree with the purpose, and (2) the participants have had skills in fish processing, especially in making bandengfish  presto, fish meatballs, fish noodles, fish shredded, and fish ketchup.Key words:   fish  processing,  and  increase of fisherman   income